Implementation of Shooting Method BEEF Concept to Basketball Shooting Skill on Foundation Magic Kids of Lubuklinggau - Anti, Devi Ari; Supriyadi, Muhammad (Universitas Suryakancana, 2021)
This research was conducted because it was not known that shooting practice with the BEEF concept was to improve basketball shooting skills at the Magic Kid Foundation Club Lubuklinggau, therefore this study aimed to determine the application of shooting practice with the BEEF concept to basketball shooting skills at the Magic Kid Foundation Club Lubuklinggau. This research is an experimental study in the form of one group pretest-posttest design, a sample of 14 athletes was then given treatment in the form of training with the BEEF concept. The instrument used was a shooting skill test for the Lubuklinggau Magic Kid Foundation athletes. The data analysis technique used is Paired Sample t-test. The results of this study have a significant effect on the t value for basketball shooting results of 15.960 with a probability (sig.) of 0.000. sign value. (2-tailed) is 0.000 < 0.05, then H0 is rejected, Ha is accepted. This means that there is a significant effect of the beef concept on Basketball Shooting Skills at Magic Kid Foundation Lubuklinggau Club. Based on the results of this processing, it can be concluded that the beef concept has an effect on basketball shooting skills at the Magic Kid Foundation Lubuklinggau Club.Keywords: Basketball BEEF Concept, and Shooting